Evidence that transient changes in sudomotor output with cold and warm fluid ingestion are independently modulated by abdominal, but not oral thermoreceptors - Morris, Nathan B. (American Physiological Society, 2014)
Two studies were performed to 1) characterize changes in local sweat rate (LSR) following fluid ingestion of different temperatures during exercise, and 2) identify the potential location of thermoreceptors along the gastrointestinal tract that independently modify sudomotor activity. In study 1, 12 men cycled at 50% V̇o(2peak) for 75 min while ingesting 3.2 ml/kg of 1.5°C, 37°C, or 50°C fluid 5 min before exercise; and after 15, 30, and 45-min of exercise. In study 2, 8 men cycled at 50% V̇o(2peak) for 75 min while 3.2 ml/kg of 1.5°C or 50°C fluid was delivered directly into the stomach via a nasogastric tube (NG trials) or was mouth-swilled only (SW trials) after 15, 30, and 45 min of exercise. Rectal (T(re)), aural canal (T(au)), and mean skin temperature (T(sk)); and LSR on the forehead, upper-back, and forearm were measured. In study 1, T(re), T(au), and T(sk) were identical between trials, but after each ingestion, LSR was significantly suppressed at all sites with 1.5°C fluid and was elevated with 50°C fluid compared with 37°C fluid (P < 0.001). The peak difference in mean LSR between 1.5°C and 50°C fluid after ingestion was 0.29 ± 0.06 mg·min(−1)·cm(−2). In study 2, LSR was similar between 1.5°C and 50°C fluids with SW trials (P = 0.738), but lower at all sites with 1.5°C fluid in NG trials (P < 0.001) despite no concurrent differences in T(re), T(au), and T(sk). These data demonstrate that 1) LSR is transiently altered by cold and warm fluid ingestion despite similar core and skin temperatures; and 2) thermoreceptors that independently and acutely modulate sudomotor output during fluid ingestion probably reside within the abdominal area, but not the mouth.